Global Impact of the COVID-19 Pandemic on Stroke Volumes and Cerebrovascular Events: A 1-Year Follow-up. (24th January 2023) - Nguyen, Thanh N.; Qureshi, Muhammad M.; Klein, Piers; Yamagami, Hiroshi; Mikulik, Robert; Czlonkowska, Anna; Abdalkader, Mohamad; Sedova, Petra; Sathya, Anvitha; Lo, Hannah C.; Mansour, Ossama Yassin; Vanguru, Husitha Reddy; et al.
Abstract : Background and Objectives: Declines in stroke admission, IV thrombolysis (IVT), and mechanical thrombectomy volumes were reported during the first wave of the COVID-19 pandemic. There is a paucity of data on the longer-term effect of the pandemic on stroke volumes over the course of a year and through the second wave of the pandemic. We sought to measure the effect of the COVID-19 pandemic on the volumes of stroke admissions, intracranial hemorrhage (ICH), IVT, and mechanical thrombectomy over a 1-year period at the onset of the pandemic (March 1, 2020, to February 28, 2021) compared with the immediately preceding year (March 1, 2019, to February 29, 2020). Methods: We conducted a longitudinal retrospective study across 6 continents, 56 countries, and 275 stroke centers. We collected volume data for COVID-19 admissions and 4 stroke metrics: ischemic stroke admissions, ICH admissions, IVT treatments, and mechanical thrombectomy procedures. Diagnoses were identified by their ICD-10 codes or classifications in stroke databases. Results: There were 148, 895 stroke admissions in the 1 year immediately before compared with 138, 453 admissions during the 1-year pandemic, representing a 7% decline (95% CI [95% CI 7.1–6.9]; p < 0.0001). ICH volumes declined from 29, 585 to 28, 156 (4.8% [5.1–4.6]; p < 0.0001) and IVT volume from 24, 584 to 23, 077 (6.1% [6.4–5.8]; p < 0.0001). Larger declines were observed at high-volume compared with low-volume centers (all p < 0.0001). There was no significant change in mechanical thrombectomy volumes (0.7% [0.6–0.9]; p = 0.49). Stroke was diagnosed in 1.3% [1.31–1.38] of 406, 792 COVID-19 hospitalizations. SARS-CoV-2 infection was present in 2.9% ([2.82–2.97], 5, 656/195, 539) of all stroke hospitalizations. Discussion: There was a global decline and shift to lower-volume centers of stroke admission volumes, ICH volumes, and IVT volumes during the 1st year of the COVID-19 pandemic compared with the prior year. Mechanical thrombectomy volumes were preserved. These results suggest preservation in the stroke care of higher severity of disease through the first pandemic year. Trial Registration Information: This study is registered under NCT04934020.